DEVELOPMENT OF GIS-BASED LEARNING MULTIMEDIA TO IMPROVE SPATIAL THINKING ABILITY OF SOCIAL STUDENTS IN HIGH SCHOOL - Rahma Azzahra; Chatarina Muryani; Gentur Adi Tjahjono (GeoEco, 2023)
Distance learning that occurred during the Covid-19 period caused problems. Learning geography, which should provide a good quality of spatial thinking, finally gets a problem. Multimedia learning is a representation tool needed in online learning. These conditions improve students' spatial thinking skills by applying Geographic Information Systems (GIS). The development of the learning multimedia uses a 4-D (Four-D) product development model consisting of the phases: define, design, development, and dissemination. Assessment parameter evaluation improves students' spatial thinking skills, considering comparing values between the experimental and control classes using the Independent Sample T-test = 0.05. The results of this study are that GIS-based learning multimedia is feasible to use with the validity test and trial being a score of 4 or is effectively used to improve students' spatial thinking skills with the result = 5,850 > T-table (2,035).